2019
DOI: 10.3847/1538-4357/ab0376
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Magnetic Field Morphology Using the Velocity Gradient Technique in the Presence of CO Self-absorption

Abstract: Probing magnetic fields in self-gravitating molecular clouds are generally difficult even with the use of the polarimetry. Based on the properties of magneto-hydrodynamic (MHD) turbulence and turbulent reconnection, Velocity Gradient Technique (VGT) provides a new way in tracing magnetic field orientation and strength based on the spectroscopic data. Our study tests the applicability of VGT in various molecular tracers, e.g. 12 CO, 13 CO, and C 18 O. By inspecting synthetic molecular line maps of CO isotopolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…While we only have two gas tracers, the available high S/N Planck data in the region allows us to draw a global picture of the interplay between the molecular cloud and the magnetic field. Hsieh et al (2019) showed that the VGs could safely be applied to both optically thin and optically thick gas tracers to infer the magnetic field morphology. In the northern part, the IGs and VGs derived from 12 CO and 13 CO data (Fig.…”
Section: Toward a Cloud Tomographymentioning
confidence: 99%
“…While we only have two gas tracers, the available high S/N Planck data in the region allows us to draw a global picture of the interplay between the molecular cloud and the magnetic field. Hsieh et al (2019) showed that the VGs could safely be applied to both optically thin and optically thick gas tracers to infer the magnetic field morphology. In the northern part, the IGs and VGs derived from 12 CO and 13 CO data (Fig.…”
Section: Toward a Cloud Tomographymentioning
confidence: 99%
“…8, we provide a brief description of the gradient dispersion and how this can be used for deriving M A . We use three super-sonic MHD simulations with different M A and apply radiative transfer code SPRAX 30 to them (see Lazarian et al (2018) 31 for details about the numerical cubes). The Supplementary Fig.…”
Section: /14mentioning
confidence: 99%
“…The VGT has been numerically tested for a wide range of column densities from diffuse transparent gas 19,28,29 to molecular self-absorbing dense gas 30 . It was shown to be able to provide both the orientations of the magnetic field as well as a measure of media magnetization 31,32 .…”
mentioning
confidence: 99%
“…4, v 0 is the velocity corresponding to the peak position in PPV's velocity profile. The validity of these two methods have been test in both numerical simulations (Hsieh et al 2019;Lazarian & Yuen 2018a) and observational data (Hu et al 2019b,a).…”
Section: Probability Density Functionmentioning
confidence: 99%
“…The ability of VGT to trace magnetic fields in turbulent media has been tested in numerical simulations (Hsieh et al 2019;Hu et al 2018;Yuen & Lazarian 2017b) and by comparing with observational polarization maps (Hu et al 2019a,b;González-Casanova & Lazarian 2019;Hu et al 2020a). These studies also reveal that a new effect takes place in the presence of self-gravity.…”
Section: Introductionmentioning
confidence: 99%